Transformations of nitrogen from velvet bean and urea used as fertilizers in corn crop - Scivittaro, Walkyria Bueno; Muraoka, Takashi; Boaretto, Antonio Enedi; Trivelin, Paulo César Ocheuze (Pesquisa Agropecuaria Brasileira, 2003)
The use of green manure's along with mineral fertilizers as crop N source is a promising management technic, that aims to make the use of mineral sources more efficient, without yield losses. The objective of this work was to evaluate the dynamics of N from velvet bean green manure and urea, applied sole or combined, to corn crop. The treatments were: 15N labeled velvet bean (113.5 kg ha-1 of N); 15N labeled urea (50 and 100 kg ha-1 of N); and the combinations of velvet bean and urea labeled or not with 15N. The experimental design was a randomized block with seven treatments and four replicates. Corn was sown 15 days after green manure incorporation to the soil. Urea was applied to the corn crop at sowing and side-dressed. Urea N recovery by corn (43%) was greater than that of green manure (12%), evidencing the superiority of urea as N source for corn crop. More N from velvet bean green manure (50%), comparing to urea (33%), remained in soil after corn cultivation. Urea N recovery in the soil-plant system (76%) surpassed that of green manure (61%). The remainder N was lost from the soil-plant system. The combination with green manure benefits urea N recuperation in the soil-plant system.